Políticas públicas educacionais para a equidade de gênero : possibilidades de práticas democráticas - Maldaner, Luciane (2023)
The dissertation titled "Educational Public Policies for Gender Equity: Possibilities and Democratic Practices," developed within the scope of the Educational Policies line of the Graduate Program in Education at UPF, aims to understand the historicity of discourses and practices structured in patriarchy that naturalize discriminatory actions against women and the LGBTQIAPN+ community. In this way, it allows us to consider the transformative power of a public, secular, and democratic education that questions antidemocratic discourses legitimizing violence against women, anchored in principles that define themselves as defenders of family and Christian morality. The research intends to historicize the foundations of the discriminatory patriarchal culture, which naturalize gender exclusion, by connecting the analysis of the role that educational policies play in the consolidation of a democratic-emancipatory perspective on education. Therefore, in addition to understanding educational public policies for gender equity as a power to realize citizen and democratic relationships, alternatives are proposed to the barriers that researchers and teachers face in a context of moral panic around the analytical category of "gender." The methodology that guided the work privileged a qualitative perspective, anchored in bibliographic and documentary sources of educational policies, as well as some statistical data on gender discrimination and violence. The research is structured into three chapters, in addition to the introduction and conclusion. The first chapter aims to analyze, on the one hand, the cultural structure of patriarchy and how it remains alive and current, generating violence and discrimination; on the other hand, it seeks to demonstrate that there are also spaces for historical struggles in defense of gender equity. The second chapter examines educational policies in defense of gender equity, that is, the legal frameworks that guarantee equality rights for women and all citizens. It seeks to show that there have been several political and educational achievements in defense of gender equality. The National Conferences on Education, as well as the National Education Plan (2014-2024), attest to these advances. However, it is indicated that gradually, these gains have been eroded by antidemocratic, homophobic, and exclusionary discourses, policies, and practices. The third chapter moves in this direction and seeks to consider education as a possibility to confront Bolsonarism and its rhetoric of hate. The research provided conditions for self-reflection on gender oppression, as well as for thinking about existing tools that allow progress in an education that ensures fundamental rights. These tools also help overcome a belief system responsible for the rise of the far right and its repertoire of Fake News regarding the supposed "Gender Ideology," "Gay Kit," and "School Without Party," phenomena based on an authoritarian and antidemocratic subjectivity. It is concluded that the feminist perspective on power relations structured in male domination enables the consideration of democratic educational practices for gender equity, both in the scope of educational public policies for gender equity and in feminist teaching practices, a scenario that can only be realized in a democratic state.